ANALISIS PERBANDINGAN EKUITAS MEREK TERHADAP PRODUK LIPSTIK WARDAH DAN LIPSTIK PIXY - Nuroh Nuroh; Naely Azhad; Akhmad Fahrur Rozi (Universitas Bandar Lampung (UBL), 2021)
Brand is a very important component, especially in an era where there has been increasingly sharp competition among the products (and services) offered by the company. The brand is an important component, because the brand is a source of information for consumers in identifying a product and differentiating that product from competing products. With this fact, making brands need to get attention and be considered as a formidable weapon in winning the competition, besides being able to be used to show a product's superiority over other products. This study aims to determine the comparison of brand equity to Wardah lipstick and Pixy lipstick products. The population in this study were students of the management economics faculty at the Muhammadiyah University of Jember with a total sample of 100 respondents using purposive sampling method. Data were collected by distributing questionnaires to measure 20 indicators. The analysis technique used is the Difference Test analysis with SPSS 23. The results of this study indicate that the three elements of brand equity between Wardah and Pixy are brand awareness, brand loyalty, and brand association which have no significant difference but the perceived quality has a significant difference.